How does individual variation in sociality influence fitness in prairie voles?. (May 2020) - Sabol, Anne C.; Lambert, Connor T.; Keane, Brian; Solomon, Nancy G.; Dantzer, Ben
Abstract : Comparative studies aid in our understanding of specific conditions favouring the initial evolution of different types of social behaviours, yet there is much unexplained intraspecific variation in the expression of social behaviour that comparative studies have not yet addressed. The proximate causes of this individual variation in social behaviour within a species have been examined in some species but its fitness consequences have been less frequently investigated. In this study, we quantified the fitness consequences of variation in the sociality of prairie voles, Microtus ochrogaster . We characterized sociality of voles in seminatural enclosures using an automated behavioural tracking system paired with social network analyses to quantify the degree of spatial and temporal co-occurrence of different voles. We then assessed the relationship between sociality and both mating success (number of different conspecifics with which an individual produced offspring) and reproductive success (total number of offspring surviving to first capture). We measured the number of social connections each individual had with all voles and with only opposite-sex voles (unweighted degree) through social network analyses. Both female and male voles varied in the number of social connections they had with all conspecifics and with opposite-sex conspecifics. In both analyses, females and males with an intermediate number of social connections had higher mating success overall and, for the analysis with all connections, produced more offspring. Males with many or few social connections also had the lowest average body mass. Overall, our results suggest some limit on the fitness benefits of sociality. Although there was substantial individual variation in our measure of vole social behaviour, intermediate levels of social connections may be most favourable. Highlights: Prairie voles exhibit substantial within-species variation in social behaviour. We examined the fitness consequences of individual variation in social behaviour. Voles with an intermediate level of sociality had the highest mating success. Voles with intermediate sociality with all voles had higher reproductive success. Males with an intermediate number of social connections had higher mean body mass.